O Tiranicídio em Tomás de Aquino - Bêco, Artur Castro Brasil (2023)
This work presents an analysis about the notion of tyrannicide in Thomas Aquinas (1224/25-1274), in order to assess the morality of the act. The research is primarily based on three major works by the author: the Summa Theologiae (1265-1273), the Scriptum Super Sententiis (1252-1254) and the De Regno ad Regem Cypri (1271/73). Tyrannicide involves several problems in Christian ethics: it considers questions of authority and obedience in the analysis of an abrupt and violent act, characterized by the stunting of the ruler's life. Can this act be morally valid? It was found that Thomas Aquinas presents, in the Scriptum Super Sententiis lib. 2 d. 44 q. 2 a.m. 2 ad 5, a position quite favorable to tyrannicide, as long as it is a last resort and in very specific situations. On the other hand, in Summa Theologiae IIª-IIae q. 64, Thomas Aquinas similarly deals with the possibility of tyrannicide in a more comprehensive way when dealing with the homicide of the malefactor, whereas, in De Regno, lib.1, chap.7, the practice is discouraged by the philosopher. It concludes by favoring the practice in the case of the tyrant who usurps power, according to the example treated in the Scriptum Super Sententiis. However, Aquinas advises against the practice when the legitimate ruler degenerates into tyranny. In this case, resistance being allowed, tyrannicide would only be possible through the execution of the ruler by the public authority.